On the controversy about the efficacy of the antimeningococcal B vaccine: methodological pitfalls - Eduardo de A. Costa
The present communication analyses methodological problems related to evaluating the protection given by the antimeningococcal B vaccine to children under four years of age in a case-control study carried out in Sao Paulo, Brazil. Detection of a hospital selection bias, among other disturbing features of the study, suggests that the efficacy of the vaccine was underestimated. Altogether, data presented support a wider use of the Cuban-produced vaccine to reduce morbidity and mortality from serogroup B meningococcal disease.